Perezhivanie and the Dramatic Event as Analytical Instruments - Liberali, Fernanda Coelho; Fuga, Valdite Pereira (The ESPecialist, 2025)
This article investigates data selection in qualitative research in education through the Vygotskian concepts of dramatic event and perezhivanie, articulated with Critical Collaborative Research (PCCol) (Magalhães, 2009, 2010, 2014). The qualitative methodology, grounded in the Socio-Historical-Cultural Activity Theory (CHAT) (Vygotsky, 1994; Leontiev, 1978), and Historical-Dialectical Materialism (Marx & Engels, 2006), emphasizes the collective production of data as discursive and multimodal processes. Four studies from the Research Group Language in Activities in School Contexts (Kemmer, 2018; Barrozo, 2019; Amorim, 2023; Lopes, 2023) were analyzed, which highlight how episodes of exclusion, pedagogical dilemmas, critical reflections, and intercultural challenges were configured as dramatic events refracted through the participants’ perezhivanie. These moments revealed affective, cognitive, pedagogical, and intercultural transformations, constituting turning points in the formation of individuals and collectives. The results indicate that the centrality of dramatic events in data selection makes explicit the potential of PCCol and contributes to understanding and transforming educational practices towards more critical, inclusive, and collaborative processes.